1995
DOI: 10.1080/07315724.1995.10718524
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-fetal transfer of ionized serum magnesium during the stress of labor and delivery: a human study.

Abstract: The observation that UAS levels of IMg2+ and TMg were similar to the MVS levels on admission despite the fall in maternal levels during labor points to the presence of homeostatic mechanisms in the fetus and placenta. It is possible that the presence of a higher fraction of unbound, free magnesium in UVS enhances magnesium transport to the fetus and thus homeostasis. Finally, we hypothesize that the fall in the levels of the biologically active form of Mg during labor may be yet another manifestation of the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Others have made similar observations. 38 Moreover, we found that the magnesium gradient was even greater (17%; P ¼ 0.001) in the setting of MgSO 4 tocolysis. 39 Thus, although obstetricians tend to make clinical decisions based on circulating magnesium levels in the mother, those in the fetus appear to be substantially higher and, thus, potentially more harmful, especially given the current state of our evolving knowledge.…”
Section: Magnesium Clearance In Babiesmentioning
confidence: 72%
“…Others have made similar observations. 38 Moreover, we found that the magnesium gradient was even greater (17%; P ¼ 0.001) in the setting of MgSO 4 tocolysis. 39 Thus, although obstetricians tend to make clinical decisions based on circulating magnesium levels in the mother, those in the fetus appear to be substantially higher and, thus, potentially more harmful, especially given the current state of our evolving knowledge.…”
Section: Magnesium Clearance In Babiesmentioning
confidence: 72%
“…At cord Mg concentrations between 4 and 11 mg/dl, respiratory depression and motor depression have been observed. Clinically, serum Mg concentration in newborn infants usually exceeds maternal levels and leads to hypermagnesemia, with cord concentrations 70-100% higher than the maternal levels [19,[22][23][24] . Our study showed an initial rapid increase in the maternal magnesium concentration followed by a gradual increase in the fetal Mg concentration during the 3 h after MgSO 4 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and magnesium placental transfer is highly regulated by hormonal mechanisms in the mother, the placenta and the foetus. Serum concentrations of these cations are high at birth (8,9). Insofar as their relationship with lipids is concerned, epidemiological studies indicate that high dietary magnesium values are correlated with high serum high-density lipoproteincholesterol (HDL-cholesterol) and low serum total lipid levels (10).…”
mentioning
confidence: 99%